Pengembangan Metode Induksi Tukak Lambung - Saputri, Fadlina Chany; Sari, Santi Purna; Munim, Abdul (UI Scholars Hub, 2008)
Scientific evaluation on pharmacological activity of medicinal herbs required repro-ducible and valid method-induced ulcer models in animal. In this study, the method of antiulcerogenic effect was investigated using several inducers. The male white Sprague-Dawley rats divided into five groups which were orally administrated water, indomethacin (48 mg/kg bw), aspirin-HCl (150 mg/kg bw), 96% ethanol (1 ml/200 g bw), and 80% ethanol (1 ml/200 g bw), respectively. The result of this study showed that the group was induced with 80% ethanol demonstrated the highest ulcer index. Histological examination of the stomach showed abnormality of mucosa cells on the aspirin-HCl, 96% ethanol, and 80% ethanol-induced gastric ulcer model in rats.